The role of recent thymic emigrant‐regulatory T‐cell (RTE‐Treg) differentiation during pregnancy. Issue 10 (19th May 2015) - Wagner, Miriam I; Mai, Charlotte; Schmitt, Edgar; Mahnke, Karsten; Meuer, Stefan; Eckstein, Volker; Ho, Anthony D; Schaier, Matthias; Zeier, Martin; Spratte, Julia; Fluhr, Herbert; Steinborn, Andrea
Abstract : During pregnancy, regulatory T cells (Tregs) have a key role in maternal immune tolerance to the semi‐allogeneic fetus. Our previous results showed that the naive CD45RA + ‐Treg pool is functionally improved in pregnant women compared with non‐pregnant women. Therefore, we examined the thymic output and differentiation of CD45RA + CD31 + recent thymic emigrant (RTE)‐Tregs during normal pregnancy and in the presence of preeclampsia. With the onset of pregnancy, the composition of the total CD4 + CD127 low+/− FoxP3 + ‐Treg pool changed in the way that its percentage of RTE‐ and CD45RA − CD31 + ‐memory Tregs decreased strongly, whereas that of the CD45RA + CD31 − ‐mature naive (MN)‐Tregs did not change and that of the CD45RA − CD31 − ‐memory Tregs increased complementary. Thereby, the ratio of RTE‐/MN‐Tregs decreased from 1.0 to 0.7 leading to a significant increase in the suppressive activity of the naive CD45RA + ‐Treg pool. This effect was confirmed by re‐assembling separated RTE‐ and MN‐Tregs from non‐pregnant women in the ratio of pregnant women. The suppressive activity of both separated naive Treg subsets was equally high in non‐pregnant and pregnant women, but considerably reduced in preeclampsia patients, who showed significantly increased percentages of CD45RA − CD31 + ‐memory Tregs, but decreased percentages of RTE‐ and MN‐Tregs. Our results suggest a reduced thymic output of RTE‐Tregs during pregnancy, which causes a decrease in the ratio of RTE‐/MN‐Tregs and thus an increase in the differentiation of RTE‐Tregs towards CD45RA − CD31 − ‐memory Tregs. Presumably, this differentiation of RTE‐Tregs, which was impaired in preeclampsia patients, ensures the improved suppressive activity of the CD45RA + ‐naive Treg pool and thus retains the maintenance of pregnancy.